Correlation of Radiological Severity of Genu Osteoarthritis (Kellgren and Lawrence) with Functional Disabilities (Womac Score) - Mitha Novita; Nyimas Fatimah (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background: Osteoarthritis (OA) is a degenerative disease that most often causes functional disabilities. The complaints that most often cause functional disabilities in people with OA are pain and stiffness. The severity of OA can be seen radiologically. The aim of this study was to assess the correlation of radiological severity of OA (Kellgren and Lawrence) with functional disabilities (WOMAC score). Method: This type of research is an analytic observational study with a cross sectional design. The population who became the respondents of this study were patients suffering from knee osteoarthritis at the Medical Rehabilitation Installation of Dr. Mohammad Hoesin Hospital, Palembang in November 2018 who met the inclusion criteria. Samples were taken by consecutive sampling technique. The functional ability of the patient will be assessed using the WOMAC score and the severity of OA radiologically interpreted based on the Kellgren and Lawrence criteria. Result: Statistical test used Somer's correlation test. From 32 respondents' data, it was found that there was no significant correlation between the radiological severity of OA and functional disability (p = 0.097). Conclusion: There is no significant correlation between radiological severity of OA (Kellgren and Lawrence) with functional disabilities (WOMAC score).